Otredad dentro del capitalismo: Etnografía móvil con una migrante en una tienda de lujo de Londres en 2023 - Martucelli García, Daniela (Pontificia Universidad Católica del Perú, 2024)
This study provides a detailed analysis of the experience of a Latina migrant in the city of London. The complexities of her integration into the British capital are explored through mobile ethnography. The case of the young Peruvian girl reveals how urban mobility between the neighbourhoods of Elephant Castle and Kensington translates into a transition between social and economic worlds that influence her identity and consumption habits. Thus, the study examines the racialization she experiences and her perception of economic differences from her work at the luxury department store Harrods. These factors result in her feeling external to the capitalist system, even while being economically and legally integrated into it. The findings contribute to understanding the social, economic, and cultural dynamics affecting the lives of migrants in urban contexts.

Este estudio ofrece un análisis detallado sobre la experiencia de una migrante latina en la ciudad de Londres. A través de la etnografía móvil, se exploran las complejidades de su inserción en la capital británica. El caso de la joven peruana revela cómo la movilidad urbana entre los barrios de Elephant Castle y Kensington se traduce en una transición entre mundos sociales y económicos que influyen en su identidad y hábitos de consumo. Así, se estudia la racialización que recibe y la percepción de las diferencias económicas desde su trabajo en la tienda de departamentos de lujo Harrods. Dichos factores generan que ella se vea externa al sistema capitalista, incluso estando inserta económica y legalmente a él. Los hallazgos concluidos contribuyen a la comprensión de las dinámicas sociales, económicas y culturales que influyen en la vida de los migrantes en contextos urbanos.
Otherness within Capitalism: A Mobile Ethnography with a Migrant in a Luxury Store in London in 2023
Keywords: Mobile ethnography; Interculturality; Latino inmigration; Luxury store; London; Etnografía móvil; Interculturalidad; Migración latina; Tienda de lujo; Londres; https://purl.org/pe-repo/ocde/ford#5.04.03